Religions and Global Sustainability. A research study in Catalonia (Spain) - Albareda-Tiana, Silvia; Gas-Aixendri, Montserrat (European Journal of Sustainable Development, 2016)
There is very little scientific literature that considers the relationship between religions and an integral concept of Sustainable Development, including its three dimensions (social, economic and environmental), as proposed in the UN Sustainable Development Goals. It was necessary to conduct a study of this kind, with the aim of making visible and show with concrete data, the contribution of religions to the integral sustainability. This paper presents an empirical research in which we intend to make visible the actions performed by religious organizations in Catalonia, that have been contributing to the Sustainable Development. The study is the launching of the Sustainability and Religions Watch. This study about the contribution of religious organizations to the Sustainable Development has been made by a mixed method with two techniques for data collection: firstly, has counted the presence of indicators linked to the priority areas of Sustainable Development, from the analysis of the content of the websites of religious organizations (quantitative analysis). Moreover, semi-structured in-depth interviews were conducted to representatives of religious organizations (qualitative analysis). The study of the contribution of religions to the Sustainable Development opens new doors to interfaith dialogue because it is based on elements that are common between different beliefs. This dialogue is a path that can effectively contribute to peace. Key words: Sustainability and Religions; Interfaith dialogue; religions and social peace.